Funding mechanisms for financing vocational training: An analytical framework - Adrian Ziderman (Institute for the Study of Labor (IZA), 2016)
The paper provides an account of innovative financing mechanisms which have been adopted in many national training systems. These mechanisms aim at correcting shortcomings of conventional training finance systems in order to better meet labor market needs, improve both the quality and relevance of training provision and to contain training costs. Directions of change include a greater diversification of funding sources for skills development (including cost sharing and training levies, mainly based on company payrolls), budgeting public training centres through objective funding formulas, encouraging more and higher quality enterprise training, the development of private training markets, increased competition between public and private training providers and the establishment of independent national training funds. Autonomous national training authorities, with broad powers and sizeable stakeholder representation, can be effective in both coordinating and steering national training systems.
Keywords: I22; J08; J24; 330; demand-driven training; funding training institutions; individual learning accounts; Levy-Grant Schemes; national training authorities; payroll levies; private training provision; training finance; training funds; training subsidies; training taxes